New Properties of Dual Continuous K-g-Frames in Hilbert Spaces. (12th April 2021) - Touri, Abdeslam; Labrigui, Hatim; Rossafi, Mohamed
Abstract : The concept of frames in Hilbert spaces continues to play a very interesting role in many kinds of applications. In this paper, we study the notion of dual continuous K -g-frames in Hilbert spaces. Also, we establish some new properties.